Environmental impacts of modern agriculture - Harrison, Roy M., 1948-; Hester, R. E. (Ronald E.) (Issues in environmental science and technology, 2012)
"Modern agriculture must seek to feed the world's growing population with little or no cost to the Environment. Modern agriculture is capable of producing greater yields than ever before, but intensification of agriculture does come at a price. This comprehensive volume examines the environmental impact made by agriculture in the 21st Century, looking forward to the future with the lessons of the past. Key chapters include impacts of agriculture upon soil quality, greenhouse gas budgets, water-borne pathogens, surface water chemistry, groundwater, agricultural pesticides and the environment, balancing the environmental consequences of agriculture with the needs for food security and positive and negative aspects of agricultural production of biofuels. A fundamental reference for advanced students, researchers, practitioners and policy makers working in the field or related areas."--